Socialization And Implementation Of Economic Empowerment Through The Smart Program (Loans Without Riba) In Petapahan Jaya Village, Kampar Riau District - Meilany, Merry; Erman, Nilam; Winario, Mohd (EL-EMIR INSTITUTE, 2024)
The Economic Empowerment Program through the PINTAR Program (Loans Without Usury) in Petapahan Jaya Village, Kampar Regency, Riau, is an initiative that aims to improve community welfare through access to loans without usury. This research aims to evaluate the socialization and implementation of the program and its impact on the economic empowerment of local communities. The research method used is field study with a qualitative approach through observation, interviews and document analysis. The research results show that this program has succeeded in increasing community knowledge about sharia-based economics and providing access to loans that help small and medium entrepreneurs to develop their businesses. High community participation, effective assistance, and the active role of local government are key factors for the success of this program. The success of the PINTAR program in Petapahan Jaya Village can be used as a model for sharia-based economic empowerment programs in other areas.